MoodyTunes: a single cohort study of a music-based smartphone app for mental health and mood regulation in young people - Sandra Garrido; Zareen O'Keeffe; Anthony Chmiel; Anthony Chmiel; Katherine Boydell; Katherine Boydell; Barbara Doran; Quang Vinh Nguyen (Frontiers in Psychology, 2025)
Mental health applications (apps) are proliferating to meet the needs of the increasing numbers of young people experiencing mental health challenges. However, many mental health apps for young people are either not evidence-based or fail to engage the interest of those who are not already receiving professional help. Since music listening is an activity that many young people are drawn to when experiencing high levels of psychological distress, MoodyTunes was developed to engage young people in learning about mental health within the context of their daily music listening activities. In this single cohort study, 70 participants aged 13–25 used MoodyTunes over a 4-week period. Pre- and post-intervention measures assessed mental health literacy, coping self-efficacy, depression, anxiety, and stress levels. Results demonstrated a significant increase in mental health literacy and decreases in anxiety and stress. Depression was found to have decreased, although not at a statistically significant level. No significant change in coping self-efficacy was found. These findings suggest that MoodyTunes may be an effective tool for improving mood regulation and psychological wellbeing in young people. Future research with larger, randomized samples and a comparative control group is recommended.